Performance evaluation of office communications applications over LANs interconnected via frame relaying. - Awada, Bilal. (University of Ottawa (Canada), 1990)
The performance evaluation of the communications networks have been the main focus in the analysis of data communications in automated office environments. This thesis is aimed at the performance evaluation of different office communications applications over LANs which are interconnected via one of the latest fast packet switching techniques called frame relaying. Different LAN technologies have been examined, namely Ethernet, Token ring and AppleTalk. The T1 (1.544 Mbps) link and the 56 kbps link are used as a public services for inter-site communications. In this study, two main applications were considered: office communications which include different types of documents that pass across an office worker's desk (publications, messages, financial forms, and normal documents), and file transfer activities such as the transfer of X-RAY images or a medium size newsletter. The transfer delay, link utilization, packet size, and the number of workstations interconnected to each LAN are the main parameters used for evaluating the system performance. Results show that the 56 kbps link is best suited for office communications under normal conditions. However as inter-site traffic increases T1 should be considered. A comparison of the performance of each LAN technology is given for both applications. The results of this study should furnish any office organization with strategic insight for the planning of its communications services.
Keywords: Business Administration, General.